Addressing the Ethical Challenges of Providing Kidney Failure Care for Children: A Global Stance - Pais, Priya; Wightman, Aaron (Frontiers in Pediatrics, 2022)
Children with kidney failure require kidney replacement therapy (KRT), namely maintenance dialysis and kidney transplant. Adequate kidney failure care consists of KRT or conservative treatment with palliative care. In the context of kidney failure, children depend on parents who are their surrogate decision-makers, and the pediatric nephrology team for taking decisions about KRT or conservative care. In this paper, we discuss the ethical challenges that arise relating to such decision-making, from a global perspective, using the framework of pediatric bioethics. While many ethical dilemmas in the care of children with KRT are universal, the most significant ethical dilemma is the inequitable access to KRT in low & middle income countries (LMICs) where rates of morbidity and mortality depend on the family’s ability to pay. Children with kidney failure in LMICs have inadequate access to maintenance dialysis, timely kidney transplant and palliative care compared to their counterparts in high income countries. Using case vignettes, we highlight how these disparities place severe burdens on caregivers, resulting in difficult decision-making, and lead to moral distress among pediatric nephrologists. We conclude with key action points to change this status-quo, the most important being advocacy by the global pediatric nephrology community for better access to affordable kidney failure care for children.